Scientometrics of the use of toxic medicinal plants as a treatment and health risk (Research, Society and Development, 2024)
Objective: Through a literature review, we sought to identify and discuss the main characteristics of the theme related to poisoning by medicinal plants in species that have hallucinogenic properties. Methods: A literature review was carried out using the following databases: Online Medical Literature Search and Analysis System (MEDLINE/PUBMED), Nursing Database - Brazilian Bibliography (BDENF), Web of Science and Cochrane Library (SCOPUS), CAPES Journals and Latin American and Caribbean Health Sciences Literature (LILACS). The search was carried out using descriptors diversely recombined with the aid of the Boolean operator "and". Results: It was found that plants classified as toxic are so named because they contain bioavailable substances capable of causing metabolic alterations. Cases of poisoning cause serious inconvenience and, in more serious cases, death. The epidemiology of plant poisoning in Brazil is a public health problem, with the vast majority of reported cases occurring as a result of the presence of these plants in public environments, caused mainly by the population's ignorance of the toxic potential of a plant species. Conclusion: The lack of encouragement to better understand Alternative and Complementary Practices is due to unreliable information about the correct use of these species. Based on scientific publications, products derived from medicinal plants are considered safe for human health, provided they are used appropriately.